Author Correction: Binge Drinking among adolescents is related to the development of Alcohol Use Disorders: results from a Cross-Sectional Study. Issue 1 (December 2018) - Addolorato, Giovanni; Vassallo, Gabriele; Antonelli, Giulio; Antonelli, Mariangela; Tarli, Claudia; Mirijello, Antonio; Agyei-Nkansah, Adwoa; Mentella, Maria; Ferrarese, Daniele; Mora, Vincenzina; Barbàra, Marco; Maida, Marcello; et al.
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.